2005
DOI: 10.1038/sj.mp.4001641
|View full text |Cite
|
Sign up to set email alerts
|

Association of the dopamine transporter (DAT1) 10/10-repeat genotype with ADHD symptoms and response inhibition in a general population sample

Abstract: Association between attention-deficit hyperactivity disorder (ADHD) and the 10-repeat allele of the dopamine transporter gene (DAT1) has been reported in independent clinical samples using a categorical clinical definition of ADHD. The present study adopts a quantitative trait loci (QTL) approach to examine the association between DAT1 and a continuous measure of ADHD behaviours in a general-population sample, as well as to explore whether there is an independent association between DAT1 and performance on neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
170
7
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(187 citation statements)
references
References 81 publications
(103 reference statements)
6
170
7
1
Order By: Relevance
“…availability) in 10R (vs. 9R) allele carriers (Jacobsen et al, 2000;Fuke et al, 2001;Mill et al, 2002; Heinz et al, 2000) who, presumably, would evidence relatively decreased striatal dopamine tone. The SLC6A3/DAT1 genotype has been related to a range of mental processes, including cognitive control/attentional functions (Cornish et al, 2005;Cools, 2008;Cools and D'Esposito, 2006) and reward related processes (Dreher et al, 2009;Colzato et al, 2010), as well as the early sensory and higher order processing of acoustic novelty, as reflected in the N1 and nP3 ERPs, respectively (Garcia-Garcia et al, 2010a,b). Although the majority of data have demonstrated no differences in striatal DAT expression or DAT1 polymorphisms in schizophrenia (vs. controls), striatal DAT availability has been inversely correlated with auditory hallucinations in the acute illness (Schmitt et al, 2006), and DAT1 gene polymorphisms have been shown to play a significant role in response to clozapine (Xu et al, 2010).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…availability) in 10R (vs. 9R) allele carriers (Jacobsen et al, 2000;Fuke et al, 2001;Mill et al, 2002; Heinz et al, 2000) who, presumably, would evidence relatively decreased striatal dopamine tone. The SLC6A3/DAT1 genotype has been related to a range of mental processes, including cognitive control/attentional functions (Cornish et al, 2005;Cools, 2008;Cools and D'Esposito, 2006) and reward related processes (Dreher et al, 2009;Colzato et al, 2010), as well as the early sensory and higher order processing of acoustic novelty, as reflected in the N1 and nP3 ERPs, respectively (Garcia-Garcia et al, 2010a,b). Although the majority of data have demonstrated no differences in striatal DAT expression or DAT1 polymorphisms in schizophrenia (vs. controls), striatal DAT availability has been inversely correlated with auditory hallucinations in the acute illness (Schmitt et al, 2006), and DAT1 gene polymorphisms have been shown to play a significant role in response to clozapine (Xu et al, 2010).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…In contrast, association with these gene variants for ADHD trait measures have either not been consistently detected or have been very much weaker, 20 or researchers have imposed cut-points on their quantitative measure to generate extreme categories (e.g. Payton et al 21 and Cornish et al 22 ). However, there are some exceptions 23 and the weakness of evidence may be because there have been fewer QTL studies.…”
mentioning
confidence: 99%
“…25,27,29,34 This approach, originally suggested by Lander and Botstein 35 in the context of linkage studies, has been recommended as an efficient and effective means of detecting association with quantitative traits in large groups of subjects. [25][26][27][28][29] The power of this method depends on a number of factors, including the size of the original group, the cutoff points for selecting from the upper and lower ends of the phenotype distribution, the allele frequencies, the mode of inheritance, and the proportion of phenotypic variance explained by the polymorphism.…”
Section: Discussionmentioning
confidence: 99%